9n-6n+2n=

Simple and best practice solution for 9n-6n+2n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9n-6n+2n= equation:


Simplifying
9n + -6n + 2n = 0

Combine like terms: 9n + -6n = 3n
3n + 2n = 0

Combine like terms: 3n + 2n = 5n
5n = 0

Solving
5n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Divide each side by '5'.
n = 0

Simplifying
n = 0

You can always share this solution

See similar equations:

| 5-(2w-2)=3(3w-8) | | 4x^2=8+4x | | 48s+41stu-33Stu= | | 3Z-9=4Z-6 | | X^2=x+12 | | 9+3p-2p+5= | | 6X^2-18XY-7X+21Y= | | 7np-7np+4np+10np= | | 9m+9MN= | | 5x+23=13x-41 | | 2m+7n+m= | | Y-0.6Y=15 | | n^2-6n=0 | | 3r+6st+5r+3st-7st= | | 3x+2y=-9 | | -5x+3(3+2x)=7 | | 41p+37p+3pqr= | | x-7x+10=28 | | 20x+22+17x+18=90 | | 33n+32np+37n-45n+18np= | | 5x+3-4x= | | 7(2a-8)=4(2a-5) | | 2x-7y=19 | | 16+3y=5y+12 | | 4(3x-2)-4(x-2)=2 | | 5(b-6)+15=15 | | 6(7x-(7-2y+2x)+5y)= | | 14x-8=13x-10 | | MN+4MN+5MN-10MN+5MN= | | 1(x+1)=5 | | 1+4x^2=8X | | 6k+7=4+12k | | 9t^2+14-17t+6t-8t^2=0 | | X^2+6x=9 | | 10m-4(3m+7)+6m=0 | | 5x^10-4x^11=1 | | 91-7x=11x+15 | | 0=5x^10-4x^11-1 | | 10-10x=74-24x | | 2x+18=66 | | y=5x^10-4x^11-1 | | -73-9x=9x+17 | | 10km-km+5km-9km+3km= | | 4x+31=13x-68 | | 91-5x=10x+16 | | 2+7m= | | 5+5g= | | 8x-25=55 | | 3BC+BC+2BC+10BC-5BC= | | 3n+6p= | | x-2x+4x-8x=8 | | 3(x+5)=90 | | 3(4x+5)=-45 | | 5+2m+1= | | 7+7p= | | 4(x-6)-4(x-8)=-10 | | 7=5(1x-4)+2 | | 7q+8r-6r= | | 0.6666666y+5y=70-y | | 5x+2y=18 | | 4a+9a+2+4a= | | 2x-3y=11 | | 18=2(1g+4)+3(2g-6) | | 9+16x^2-24x=0 | | -4+6t-6= |

Equations solver categories